Consumers’ perception in possessing trendy mobile phones - Mansor, Farida Pasha; Ali Amran, Ila Norsalida; Abu Bakar, Mohamad Azhari; Abd Hamid, Mohd Syakir; Mohd. Mahudin, Nor Diana (2007)
This research is conducted to assess the relationship between the behaviour in, and the reasons for possessing trendy mobile phones among university’s consumers. Using stratified random sampling, a total of 69 participants was selected from both staff (academic and non academic) and students (local and international). A self-administered questionnaire with Cronbach’s alpha of 0.87 was used for data collection. The findings supported the hypothesis that university’s consumers are highly interested in possessing trendy mobile phones due to self-satisfaction, social acceptance, and prestige. Further analyses however failed to obtain any significant differences between perceptions of university staff with that of students’ in terms of their perception in possessing trendy mobile phones. The implications of this study on designs and preferred choices of consumers are discussed.